Adult Onset Still's Disease and Rocky Mountain Spotted Fever - Paul Persad; Rajendrakumar Patel; Niki Patel (Case Reports in Medicine)
Adult Still's Disease was first described in 1971 by Bywaters in fourteen adult female patients who presented with symptoms indistinguishable from that of classic childhood Still's Disease (Bywaters, 1971). George Still in 1896 first recognized this triad of quotidian (daily) fevers, evanescent rash, and arthritis in children with what later became known as juvenile inflammatory arthritis (Still, 1990). Adult Onset Still's Disease (AOSD) is an inflammatory condition of unknown etiology characterized by an evanescent rash, quotidian fevers, and arthralgias. Numerous infectious agents have been associated with its presentation. This case is to our knowledge the first presentation of AOSD in the setting of Rocky Mountain Spotted Fever. Although numerous infectious agents have been suggested, the etiology of this disorder remains elusive. Nevertheless, infection may in fact play a role in triggering the onset of symptoms in those with this disorder. Our case presentation is, to our knowledge, the first case of Adult Onset Still's Disease associated with Rocky Mountain spotted fever (RMSF).